PENGARUH PROFITABILITAS TERHADAP AGRESIVITAS PAJAK PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL MODERASI - Wardah, Afifah Mutia; Hamdi, Mukhlizul; Fauziati, Popi; Karimi, Kasman (POLITEKNIK LP3I JAKARTA, 2023)
The purpose of this study was to empirically determine the effect of profitability by proxies Return On Assets (ROA), Return On Equity (ROE) and Return On Sale (ROS) on tax aggressiveness with Corporate Social Responsibility (CSR) as a moderating variable. The sample for this study was mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period, using a non-probability sampling method with a purposive sampling technique which produced 20 sample companies. In testing the hypothesis using Moderated Regression Analysis (MRA). The results of this study are only ROS which has a positive effect on tax aggressiveness, while ROA, ROE and CSR have no effect on tax aggressiveness. CSR is not able to moderate the relationship between ROA, ROE and ROS on tax aggressiveness. The only control variable is company size which has an effect on tax aggressiveness, while firm size and leverage have no effect on tax aggressiveness. Keywords: Return On Asset (ROA), Return On Equity (ROE), Return On Sales (ROS), Corporate Social Responsibility (CSR), Tax Aggressiveness